2020
DOI: 10.1016/s0140-6736(20)30058-1
|View full text |Cite|
|
Sign up to set email alerts
|

Accelerated surgery versus standard care in hip fracture (HIP ATTACK): an international, randomised, controlled trial

Abstract: Background: Observational studies have suggested that accelerated surgery is associated with improved outcomes in patients with a hip fracture. The HIP ATTACK trial assessed whether accelerated surgery could reduce mortality and major complications. Methods:We randomised 2970 patients from 69 hospitals in 17 countries. Patients with a hip fracture that required surgery and were ≥45 years of age were eligible. Patients were randomly assigned to accelerated surgery (goal of surgery within 6 hours of diagnosis; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 235 publications
(108 citation statements)
references
References 31 publications
4
99
3
2
Order By: Relevance
“…new clinical pathway with PCR testing) had a disadvantageous effect on the ability to provide timely hip fracture care. Although accelerated surgery (< 6 h) has not proved to help decrease morbi-mortality rate, hip fractures should not wait for more than 24-48 hours to undergo surgery [29]. Whether the delay is higher than 48 hours, the risk of three day and one year mortality is significantly increased [30].…”
Section: Discussionmentioning
confidence: 99%
“…new clinical pathway with PCR testing) had a disadvantageous effect on the ability to provide timely hip fracture care. Although accelerated surgery (< 6 h) has not proved to help decrease morbi-mortality rate, hip fractures should not wait for more than 24-48 hours to undergo surgery [29]. Whether the delay is higher than 48 hours, the risk of three day and one year mortality is significantly increased [30].…”
Section: Discussionmentioning
confidence: 99%
“…There may also be a time point beyond which no further gains are achieved. For instance, a randomized controlled trial of patients with native hip fractures found that attempting surgery within 6 hours of diagnosis was not associated with improved outcomes compared with routine care which was 24 hours in this trial [17]. Unfortunately, given the limitations of small sizes and heterogeneity within patients with periprosthetic hip fractures, using retrospective data to identify an inflection point or obtaining prospective data to test an intervention may not be feasible.…”
Section: Discussionmentioning
confidence: 88%
“…In the recent publication of the randomised controlled trial of the HIP ATTACK investigators there was no benefit in accelerated surgery within 6 hours after diagnosis compared with 24 hours (standard care group 10-42 hours). 30 We want to measure and validate the optimal time to surgery within the 48 hours before the risk of postoperative complications increases. Moreover, we wish to study whether the time to surgery should be strictly within 24 hours on admission or can be extended to 48 hours.…”
Section: Preoperative Carementioning
confidence: 99%